(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2015)
ORBIS is a global database and financial analysis tool offering company statements, ownership, rating and scores, news and intelligence. Global means the current coverage exceeds 165 million entities which most of them are private companies. However also listed companies, banks (over 35.000), insurance companies are included. And all that taking into consideration how different the legislations in countries are sometimes not only giving the free choice to companies when it comes to publish the reports but also forbids to do so (some Islamic jurisdictions). Goal of the paper is to demonstrate the usage of ORBIS in the examination of the capital structure of the Hungarian and French wine industry. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.